Association between pregnancy-induced hypertensive fundus changes and fetal outcomes - Karki, P; Malla, P; Das, H; Uprety, DK (Nepalese Journal of Ophthalmology, 2010)
Background: Ocular involvement in pregnancy-induced hypertension (PIH) is common. Objective: To study the association between pregnancy-induced hypertensive fundus changes and fetal outcomes. Subjects and methods: A prospective cohort study was carried out including 153 subjects with the diagnosis of PIH. The subjects were evaluated for hypertensive fundus changes. Fetal outcomes were assessed in terms of gestational age, birth weight, 1 minute Apgar score, stillbirth and neonatal death. Statistics: The chi 2 test was used to evaluate the association between the various fundus changes and fetal outcomes using SPSS version 10 software program. Results: Fundus changes were found in 13.7 % of the subjects. The means of systolic and diastolic BP of the subjects with hypertensive fundus changes were 182.86 ± 33.64 and 125.24 ± 21.36 respectively, whereas those values without fundus changes were 150.72 ± 12.86 and 100.07 ± 9.51.Vitreous hemorrhage, serous retinal detachment and macular star were not found in this study. Fetal outcomes in PIH patients with vascular changes alone were similar to those with no fundus changes. Retinal and optic nerve head changes were found to be associated (p =0.016) with low birth weight (<2.5 kg). Choroidal changes and optic nerve head changes were associated with low Apgar score. Conclusion: Retinal and optic nerve head changes are associated with low birth weight. Choroidal changes and optic nerve head changes are associated with low Apgar score. Fundus evaluation in patients with PIH is an important procedure to predict adverse fetal outcomes. Keywords: PIH; retinopathy; choroidopathy; optic neuropathy; fetal outcomes. DOI: 10.3126/nepjoph.v2i1.3700 Nep J Oph 2010;2(1):26-30